Real-time Monitoring of Aerosol Generating Dental Procedures. (May 2022) - Fennelly, Mehael; Gallagher, Catherine; Harding, Mairead; Hellebust, Stig; Wenger, John; O'Sullivan, Niall; O'Connor, David; Prentice, Michael
Abstract: Objective: We aimed to quantify aerosol concentrations produced during different dental procedures under different mitigation processes. Method: Aerosol concentrations were measured by the Optical Particle Sensor (OPS) and Wideband Integrated Bioaerosol Sensor (WIBS) during routine, time-recorded dental procedures on a manikin head in a partitioned enclosure. Four different, standardised dental procedures were repeated in triplicate for three different mitigation measures. Result: Both high-volume evacuation (HVE) and HVE plus local exhaust ventilation (LEV) eradicated all procedure-related aerosols, and the enclosure stopped procedure-related aerosols escaping. Aerosols recorded by the OPS and WIBS were 84 and 16-fold higher than background levels during tooth 16 FDI notation (UR6) drilling, and 11 and 24-fold higher during tooth 46 FDI notation (LR6) drilling, respectively. Ultrasonic scaling around the full lower arch (CL) or the full upper arch (CU) did not generate detectable aerosols with mitigation applied. Without mitigation the largest concentration of inhalable particles during procedures observed by the WIBS and OPS was during LR6 (139/cm 3 ) and UR6 (28/cm 3 ) drilling, respectively. Brief aerosol bursts were recorded during drilling procedures with HVE, these did not occur with LEV, suggesting LEV provides protection against operator errors. Variation was observed in necessary fallow times (49 – 280 minutes) without mitigation, while no particles remained airborne when mitigation was utilised. Conclusion: This data demonstrates that correctly positioned HVE or LEV is effective in preventing airborne spread and persistence of inhalable particles originating from dental AGPs. Additionally, a simple enclosure restricts the spread of aerosols outside of the operating area. Clinical significance: Employing correctly positioned HVE and LEV in non-mechanically ventilated clinics can prevent the dispersal and persistence of inhalable airborne particles during dental AGPs. Moreover, using enclosures have the additive effect of restricting aerosol spread outside of an operating area.